Talking Local: Florida Consumers’ Flexibility with the Term "Local" - Joy N. Rumble; Caroline G. Roper (EDIS)
This is a minor revision of an EDIS publication focusing on Florida consumer flexibility with the term “local.” It is the fifth in a six-part series about Florida consumers and their perceptions of local food. The Talking Local series focuses on ways Extension agents can assist Florida farmers and ranchers in the labeling, sale, and promotion of locally produced products. This series provides Extension faculty who are interested in local food programming or who work with local food clientele with information about Florida consumers’ perceptions of local food. This 4-page publication was written by Joy N. Rumble and Caroline G. Roper, and published by the Department of Agricultural Education and Communication, November 2017.